Pawel Kozłowski’s Unknown Letter to Mathias Casimirus Sarbievius - Nedzinskaitė, Živilė (Senoji Lietuvos literatūra, 2015)
The canon of Mathias Casimirus Sarbievius’ poetical works has been established long since. It consists of four books or lyric poems, one book of epodes, one book of epigrams, the poem Iter Romanum, a fragment of the epos Lechiada, and several panegyrics. His treatises on literary theory De perfecta poesi and Praecepta poetica, and the work on classical mythology Dii gentium were published in the twentieth century. However, his work on theology is still in the manuscript form. Not much is known on the poet’s epistolographic legacy although it was quite abundant and engaging.The best know at present is Sarbievius’ correspondence with the bishop of Plock Stanisław Łubieński (1573–1640), and the recently published interesting exchange of letters between Sarbievius and Janusz Radziwiłł (1612–1655). The poet’s connections with Dutch Jesuits (Jean Bolland and others), the publisher from Antwerp Balthasar Moretus (1574–1641) are also well known. Sarbievius corresponded with figures of West European academia, but only Dionysius Petavius’ letter to Sarbievius is known today.In this paper the author focuses on the copy of a 1633 letter written to Sarbievius by Paweł Kozłowski (Paulius Kozlovskis, Paulus Coslovius, 1592/93–1651), who studied with the poet in Vilnius. The copy of the letter is kept at the Archives of the House of the Superior General (Archivum Romanum Societatis Iesu, ARSI). It tells about how Nicolaus Lancicius, Provincial Superior of Lithuania, miraculously cured the castellan of Sierpc Kuczborski and his daughter Mariana.Kozłowski’s letter is interesting and important in several aspects. First of all, it is yet another testimony to Sarbievius’ abundant correspondence on an impressive variety of subjects. In this case the poet is addressed as an individual who could testify to the miracles of Father Lancicius and to elucidate such things to people who did not believe in such things or rejected their possibility. There emerges a yet unrecorded fact of Sarbievius’ biography: he took a personal interest in Lancicius’ activities. The second aspect is that the circle of Sarbievius’ correspondents becomes broader and now includes Father Kozłowski. Third, the letter is a direct testimony to Lancicius’ ability to cure people and contributes to a multitude of descriptions and evidence of this nature. Fourth, one Jesuit’s letter to another about a third member of the Society of Jesus, the Provincial Superior, is an additional source of the history of the Lithuanian Society of Jesus.
Keywords: -